Innovative Baggage Delivery Services In Future air transport networks - SARAH AL-HILFI (2020)
Airports must accommodate ever increasing passenger numbers while offering a wide range of services. The services are provided through different facilities and processes creat-ing a complex ecosystem of mutually dependent activities. Airport terminals are large-size multi-stakeholder buildings with innovative designs. The complex management of all air-port operations requires proper recognition of all relationships among many stakeholders. The overarching aim of the management and design efforts so to provide high level of passenger satisfaction, and at the same time, to ensure smooth operations with minimum delays. The demands to accommodate increases in passenger numbers drive the need for expanding the capacity of airport and for using the resources and infrastructure more ef-ficiently. The imbalance between the services demand and the available capacity creates congestion problems at different service points throughout the airport. Unlike many other previous works addressing mainly the airport capacity and congestion related to the num-ber of aircraft and flights it is able to serve at any one time, our work is concerned with passenger services, and specifically with baggage delivery. More specifically, the concept of dissociating passenger travel from baggage delivery is introduced and evaluated from several different perspectives. The baggage dissociation can help to improve the passenger air travel experience, make public transport to airport more viable option, and thus, reduce ground-side congestion at airports with reduced CO2 emissions, use existing airport capaci-ty more efficiently while reducing footprint of new airports, optimize monetization of cargo and baggage delivery, elevate the value of non-hub airports, and exploit the new aircraft designs to name a few. It can be argued that innovations in baggage delivery will be man-datory in order to meet the future passenger demands. However, despite these significant drivers, at present, there are still many regulatory and infrastructure challenges which have to be overcome before baggage dissociation can become reality. This thesis contributes sev-eral studies towards feasibility of the baggage dissociation, two ways have been presented to pave the way for the baggage dissociation the new baggage delivery networks and the Satellite terminals (Off-Airport terminals).